2011
DOI: 10.1890/09-2178.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between species feeding traits and environmental conditions in fish communities: a three-matrix approach

Abstract: Understanding the relationships between species biological traits and the environment is crucial to predicting the effect of habitat perturbations on fish communities. It is also an essential step in the assessment of the functional diversity. Using two complementary three-matrix approaches (fourth-corner and RLQ analyses), we tested the hypothesis that feeding-oriented traits determine the spatial distributions of littoral fish species by assessing the relationship between fish spatial distributions, fish spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 85 publications
(133 reference statements)
0
43
1
5
Order By: Relevance
“…Using existing datasets from different sources we found significant correlations for 13%–16% of the 2508 possible correlations and significant inertias for all datasets, indicating the methods employed here are productive and match explanatory power of other fourth corner analyses of fish functional traits [50]. The trait-environment correlations observed are useful for guiding preliminary species level conservation inquiry by linking functional traits like spawning behaviors and environmental gradients like land cover.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Using existing datasets from different sources we found significant correlations for 13%–16% of the 2508 possible correlations and significant inertias for all datasets, indicating the methods employed here are productive and match explanatory power of other fourth corner analyses of fish functional traits [50]. The trait-environment correlations observed are useful for guiding preliminary species level conservation inquiry by linking functional traits like spawning behaviors and environmental gradients like land cover.…”
Section: Discussionmentioning
confidence: 54%
“…Traits of relatively moderate size at maturation, moderate fecundity, and high juvenile survivorship associated with an equilibrium strategy were correlated with geologically and climatically stable areas or rivers with increased or long histories of regulated flow. State, river drainage, and smaller scale studies found responses along gradients of elevation, drainage area, catchment land cover, suspended sediments, mesohabitat hydraulics, and substrate [13], [18], [50], [51], [52], [53], but limited changes in response to riparian buffers [52], [54]. Concordant results from similar studies in freshwater systems throughout the world, such as South America [16], [55], Europe [10], [12], [14], [56], Australia [57], and Africa [58], support the hypothesis that patterns identified in trait-based studies are repeatable among biogeographic regions.…”
Section: Introductionmentioning
confidence: 99%
“…When stressors lead to species replacement by functionally different species (i.e. In natural lakes, fish functional traits were shown to respond to environmental and pressure gradients (Brind'Amour, Boisclair, Dray, & Legendre, 2011;Erős, Heino, Schmera, & Rask, 2009). In such situation, the use of functional diversity metrics can provide additional information on the response of fish communities to stressors (Rosenfeld, 2002;Villéger, Ramos Miranda, Flores Hernández, & Mouillot, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This method links species traits to vegetation characteristics by the simultaneous ordination of the vegetation characteristics at each site (R), the species present (L), and their life-history traits (Q) and it has the advantage that multiple life-history traits can be assigned to each species. RLQ analysis has been applied to a wide range of taxa, including bat and fish assemblages in North America (Duchamp and Swihart 2008;Brind'Amour et al 2011), ground beetles in the United Kingdom (Ribera et al 2001), birds, insects and spiders in Europe (Hausner et al 2003;Le Viol et al 2008; Barbaro and van Halder 2009;Lizée et al 2011), bird assemblages in Africa (Seymour and Dean 2010), and butterflies and coral in southeast Asia (Rachello-Dolmen and Cleary 2007;Cleary et al 2009). It also has been applied to a range of human-disturbed environments, including abandoned fields (Bernhardt-Romermann et al 2008), logged forest , and urban areas (Threlfall et al 2011).…”
Section: Introductionmentioning
confidence: 99%